Relationship between Serum Homocysteine Levels and Manganese Superoxide Dismutase (MnSOD) on Retinal Nerve Fiber Layer (RNFL) Thickness in Diabetic Retinopathy and Non-Diabetic Retinopathy Patients: Oral Presentation - Observational Study - Resident - Delfi; Nurrakhmah, Rini; Lubis, Rodiah Rahmawaty; Virgayanti, Vanda (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesDiabetic retinopathy is a visual disorder caused by abnormalities in the retina, where there is aprogressive microangiopathy characterized by damage and blockage of fine blood vessels, resultingin impaired nutrition of the retina. This study is to find out the relationship between serumhomocysteine levels and MnSOD on retinal nerve fiber layer (RNFL) thickness in diabeticretinopathy and non-diabetic retinopathy patients. MethodsThis study is an analytic observational case-control study with a total of 31 subjects for each group.3cc of venous blood samples were taken to assess the serum levels of homocysteine and MnSOD andthen analyzed by ELISA method in the integrated laboratory of the USU Medical Faculty. ResultsThere was a significant difference in Avg RNFL and Nasal RNFL thickness between the two groups(p=0.015) with the mean Avg RNFL thickness being 100.94 (SD=17.04) and the mean RNFL nasalthickness being 90.16 (SD=33.68). The highest MnSOD levels were found in non-diabeticretinopathy subjects with a mean of 142.77 (SD=101.77). There was no significant relationshipbetween homocysteine and thickness of superior RNFL (p=0.346), inferior RNFL (p=0.292),temporal RNFL (p=0.109), nasal RNFL (p=0.190). However, a significant association was foundbetween homocysteine and Avg RNFL (p=0.007). ConclusionIn the group of cases of diabetic retinopathy, a significant relationship was found between Hcy andAvg RNFL (p=0.007). An increase in serum homocysteine levels will be followed by a decrease in thethickness of the Avg RNFL.